Modeling of traction power supply system and analysis on its influence on power quality of power grid - ZHU Hua; YING Yichen; LIU Shuming; DAI Shuangyin; WU Mingli (机车电传动)
In order to analyze the influence from traction power supply system harmonics of the electric multiple units (EMUs) on the power grid, a load simulation model was established, which can truly reflect the harmonic fluctuation of traction power supply system with EMU included. Based on the measured data, a fast generation method of EMUs probabilistic harmonic model was proposed and verified in this paper. With a direct traction power supply system built in MATLAB/Simulink, considering the nonlinear characteristics of transformer harmonic impedance, the law of influence from the number and location of EMUs and the short-circuit capacity of the power grid on the electric energy quality of the power grid was analyzed through simulation, and a quantitative formula was given accordingly. This formula can be used to rapidly evaluate the possible harmonics occurring when a traction power supply system is connected to the public grid, which provides a certain theoretical basis for the subsequent harmonic suppression.